Astrocyte gap junctions and Kir channels contribute to K+ buffering and regulate neuronal excitability - Bojovic, Danica; Dagostin, Andre; Sullivan, Steve J.; Emery, Ben; von Gersdorff, Henrique; Mishra, Anusha (Frontiers in Cellular Neuroscience, 2025)
Astrocytes are connected in a functional syncytium via gap junctions, which contribute to the maintenance of extracellular K+ homeostasis. The prevailing hypothesis is that K+ released during neuronal firing is taken up by astrocytes via Kir channels and then distributed among neighboring astrocytes via gap junctions. Here, we tested the effect of blocking gap junctions and Kir channels, both independently and simultaneously, on field excitability of cortical slices in response to a stimulation train. Independently blocking either gap junctions or Kir channels increased the amplitude of the first fEPSC (field excitatory post-synaptic current) response, followed by suppression of both fiber volley (pre-synaptic action potentials) and fEPSCs during sustained stimulation. Surprisingly, simultaneous block of both gap junctions and Kir channels enhanced the suppression of neuronal activity, resulting in a ∼75% decrease in fiber volley amplitude in the first response, followed by a fast and strong suppression of fEPSCs during sustained stimulation. Genetic depletion of astrocyte gap junctions showed a reduction but not complete loss of Cx43, indicating partial syncytial decoupling, and, accordingly, had a weaker but similar effect on neuronal excitability as blocking gap junctions. Pharmacological Kir block in mice with reduced gap junction coupling suppressed sustained firing of the fiber volley but not fEPSCs. That this effect was milder than Kir block alone suggests that adaptive mechanisms may be recruited upon genetically induced astrocyte decoupling. We conclude that K+ buffering via Kir and gap junctions in astrocytes together play a critical role in maintaining neuronal excitability, particularly during sustained activity, but that other mechanisms can be recruited to perform this function in their absence.